Exploring school food provision programs and links to local foods in Pacific Island countries - Perry, J.; Horsey, B.; Raneri, Jessica; Hunter, Danny; O’Connor, S.; Hyland-Wood, M.; Casey, E.; Burkhart, S. (Cambridge University Press, 2024)
Providing access to food in schools can serve as a platform for food system transformation, while simultaneously improving educational outcomes and livelihoods. Locally grown and procured food is a nutritious, healthy, and efficient way to provide schoolchildren with a daily meal while, at the same time, improving opportunities for smallholder farmers (1) . While there is significant potential for school food provision activities to support healthy dietary behaviours in the Pacific Islands region, there is limited evidence of these types of activities (2) , including scope and links to local food production in the region. Therefore, the aim of this scoping study was to understand the current state of school food activities (school feeding, gardening and other food provision activities) and any current, and potential links to local agriculture in the Pacific Islands. A regional mapping activity was undertaken, initially covering 22 Pacific Island countries. The mapping included two steps: 1) a desk based scoping review including peer-reviewed and grey literature (2007-2022) and 2) One-hour semi-structured online Zoom interviews with key country stakeholders. Twelve sources were identified, predominately grey literature (n = 9). Thirty interviews were completed with at least 1 key stakeholder from 15 countries. A variety of school food provision activities were identified, including school feeding programs (n = 16, of varying scale), programs covering both school feeding and school gardens (n = 2), school garden programs (n = 12), and other school food provision activities (n = 4, including taste/sensory education, food waste reduction, increasing canteen capacity for local foods, supply chain distribution between local agriculture and schools). Existing links to local agriculture varied for the different programs. Of the 16 school feeding programs, 8 had a requirement for the use of local produce (policy requirement n = 6, traditional requirement from leaders n = 2). Of the 12 school garden programs, 6 used local or traditional produce in the garden and 5 involved local farmers in varying capacities. Challenges to linking local agriculture into school food provision programs were reported for 17 activities and were context dependent. Common challenges included limited funding, inflation, Covid-19, inadequate produce supply for the scale of program, limited farmer capacity, limited institutional support for local produce, low produce storage life, climatic conditions and disasters, water security, delayed procurement process, and limited professional development and upskilling opportunities. Modernisation and colonisation of food systems resulting in a preference for hyperpalatable foods and challenges in incorporating local produce in a way that is accepted by students was also identified as a challenge. This evidence can be used to develop a pathway to piloting and implementing models of school food provision programs and promoting opportunities for shared learning and collaboration with key stakeholders across the Pacific Islands region.